Diversity of symbiotic bacteria associated with Bemisia tabaci (Homoptera: Aleyrodidae) in cassava mosaic disease pandemic areas of Tanzania - Tajebe, L.; Guastella, D.; Cavalieri, V.; Kelly, S.; Hunter, M.; Lund, O.; Legg, James P.; Rapisarda, Carmelo (Wiley, 2015)
All Bemisia tabaci individuals harbour an obligate bacterial symbiont (Portiera aleyrodidarum), and many also harbour non-essential facultative symbionts. The association of symbiotic bacteria with the various genetic groups of B. tabaci remains unknown for East Africa. This study aimed to assess any association between the various whitefly genetic groups and the endosymbionts they harbour; to investigate if a unique endosymbiont is associated with super-abundant whiteflies, and to provide baseline information on endosymbionts of whiteflies for a part of East Africa. Whiteflies collected during surveys in Tanzania were genotyped and screened for the presence of the obligate and six secondary symbionts (SS): Rickettsia (R), Hamiltonella (H), Arsenophonus (A), Wolbachia (W), Cardinium (C) and Fritschea (F). The results revealed the presence of Mediterranean (MED), East Africa 1 (EA1), Indian Ocean (IO) and Sub-Saharan Africa 1 (SSA1) genetic groups of Bemisia tabaci, with SSA1 further clustered into four sub-groups: SSA1-SG1, SSA1-SG2, SSA1-SG1/2 and SSA1-SG3. F was completely absent from all of the whiteflies tested while R was always found in double or multiple infections. In general, no particular symbiont appeared to be associated with the super-abundant SSA1-SG1 B. tabaci, although A or AC infections were common among infected individuals. The most striking feature of these super-abundant whiteflies, dominating cassava mosaic disease pandemic areas, was the high prevalence of individuals uninfected by any of the six SS tested. This study of the endosymbionts of B. tabaci in East Africa showed contrasting patterns of infection in crop and weed hosts.